THE EFFECTIVENESS OF HILOKAL APPLICATION ON SPEAKING SKILL FOR STUDENTS IN HIGH SCHOOL - Hartini Agustiawati; Ressy Novasyari; Na'imatul Husni; Nia Anggraini (Utan Kayu Publishing, 2024)
Language is crucial for communication and understanding in various aspects of life, including economy, education, politics, and culture. English is the dominant language, but learning it can be challenging due to native speakers' unique personalities and cultures. Speaking ability is crucial for language development and fluency in a second language, and technology like Hilokal offers new opportunities for language learners to improve their skills through interactive apps. This study uses George's library research theory and qualitative research to understand Hilokal, a language learning app that bridges the gap between formal instruction and real-life language use. The app offers interactive games, real audio recordings, and movies to expose learners to native speakers' speech patterns, addressing barriers to building speaking skills. However, Hilokal has two main drawbacks: less popularity and usability compared to popular platforms like Duolingo, and may not be suitable for young learners due to its focus on active conversation. To compete, Hilokal needs to invest in targeted marketing, optimize its user interface, collaborate with language educators, and create an age-appropriate version for young learners.